OPTIMALISASI NILAI KELAPA DENGAN MANAJEMEN MEKANISASI PERTANIAN DI KELOMPOK TANI DESA PINAMORONGAN, KAB. MINAHASA SELATAN - Dedie Tooy; Nordy Waney; Tineke Langi; Herry Pinatik; Tommy Lolowang; Sherina Laleleh; Frits Mona (Jurnal Abdimas Bina Bangsa, 2024)
Coconut plants are a superior plant in Pinamorongan Village, South MInahasa Regency. However, most of the existing coconuts are only made into copra or sold as whole coconuts, which have low value. The management aspect of mechanization is a concern because this knowledge is still low. The aim of this community service activity or community partnership program in Pinamorongan village is to provide training in optimizing management of agricultural mechanization and processing, so as to increase the value of coconut products whose value is still low. Activities are carried out by observing problems, discussions with the village government, discussions with farmers and training on optimizing existing mechanization equipment. Training on creating business models has been distributed including optimizing agricultural mechanization which has an impact on increasing farmers' income for the sustainability of their farming business. As a result of this activity, farmers become more knowledgeable and skilled in management and business aspects. Future recommendations for increasing farmers' income, apart from coconut, include developing the cultivation of high-value agricultural commodities such as vanilla and chilies